Generative AI in Financial Services: A Strategic Framework for Digital Transformation - Vijaya Kumar Guntumadugu, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article examines the transformative impact of Generative Artificial Intelligence (GenAI) on the financial services industry, with a particular focus on strategic implementation and operational transformation in the banking sector. Through a comprehensive analysis of current implementations and strategic initiatives, particularly in North American banks, the article explores how GenAI is revolutionizing traditional banking operations, from automated knowledge management to personalized customer services. The article investigates the multifaceted approach institutions are taking toward AI integration, including investments in infrastructure, talent development, and risk management protocols. The article reveals that successful AI implementation requires a balanced approach between innovation and risk mitigation, with institutions strategically deploying AI solutions across various operational domains. This article contributes to the growing body of literature on digital transformation in financial services by providing a structured framework for understanding the strategic implications of GenAI adoption and its role in shaping the future of banking operations. The article concludes by identifying critical success factors for AI implementation and suggesting future research directions in this rapidly evolving field.
Keywords: Generative AI; Financial Services; Digital Transformation; Banking Innovation; AI Strategy